Integração e modularidade como mecanismos de diversificação em gêneros de Acestrorhamphidae (Teleostei: Characiformes) - Coelho, Bruno Alves Sousa [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
The evolution of hyperdiverse groups is marked by high rates of speciation and differentiation, often driven by external factors, such as environmental changes. However, diversification also depends on internal factors, such as adaptive capacity and morphological integration. High integration means that structures evolve in a coordinated manner along a main axis, while less integrated structures evolve as independent modules. The newly proposed family Acestrorhamphidae (Teleostei: Characiformes) and its subfamilies Acestrorhamphinae, Grundulinae, and Rhoadsiinae form one of the largest clades of Neotropical fishes. Despite its high diversity, morphological variation is surprisingly limited. This study used Geometric Morphometrics, and analyses of modularity and integration to investigate the factors influencing the diversification of this group. A strong integrative effect on the body shape of the group was observed, which seems to be organized into a cranial, pre-caudal, and caudal modules. PCA revealed a limited number of morphotypes, supporting the idea of a hyperdiverse clade with conserved morphology. These results reinforce previous studies showing how morphological integration can accelerate speciation, focusing adaptation along a single evolutionary axis, while maintaining the group's morphological stability.

The evolution of hyperdiverse groups is marked by high rates of speciation and differentiation, often driven by external factors, such as environmental changes. However, diversification also depends on internal factors, such as adaptive capacity and morphological integration. High integration means that structures evolve in a coordinated manner along a main axis, while less integrated structures evolve as independent modules. The newly proposed family Acestrorhamphidae (Teleostei: Characiformes) and its subfamilies Acestrorhamphinae, Grundulinae, and Rhoadsiinae form one of the largest clades of Neotropical fishes. Despite its high diversity, morphological variation is surprisingly limited. This study used Geometric Morphometrics, and analyses of modularity and integration to investigate the factors influencing the diversification of this group. A strong integrative effect on the body shape of the group was observed, which seems to be organized into a cranial, pre-caudal, and caudal modules. PCA revealed a limited number of morphotypes, supporting the idea of a hyperdiverse clade with conserved morphology. These results reinforce previous studies showing how morphological integration can accelerate speciation, focusing adaptation along a single evolutionary axis, while maintaining the group's morphological stability
Modularity and Integration as Drivers of Diversification in Acestrorhamphidae Genera (Teleostei: Characiformes)
Keywords: Morfometria Geométrica; Integração; Modularidade; Characiformes; Characiformes; Integration; Modularity